Trinity : 450 years of an Oxford college community - Hopkins, Clare (Oxford University Press, 2005)
This history of Trinity College from 1555 until the present day illustrates the changing shape and purpose of one of Oxford's colleges: a training house for Catholic priests in the sixteenth century; a pillar of the Anglican establishment in the late seventeenth and eighteenth centuries; a centre of educational reform in the nineteenth; a thriving part of Oxford University today. Clare Hopkins makes extensive use of archival sources and the records of ordinary students to focus on the changing nature of a college community. This book exemplifies the evolution of Fellows into tutors, undergraduate commonors into students, and household servants into staff, and shows how the needs of these mutually dependent groups have shaped the environment around them.